2021
DOI: 10.3390/en14175353
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attitudes and the Attitude to Energy Saving among Young People with ASD

Abstract: The aim of the study was to determine the association between parental attitudes and saving energy in the perception of young people with autism spectrum (13–17 years old). The character of studies was pilot. The diagnostic survey method was used, along with The Scale of Parental Attitudes by M. Plopa and an authored survey questionnaire. Deliberate random sampling was applied. Statistical analysis showed that an attitude towards autonomy manifested by mothers, as well as an attitude of acceptance in mothers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Parents who involve their children in the decisions of family affairs in this way not only provide social competences, but also by adopting the values of parents they contribute to environmentally-friendly behavior. Thus, it is likely that young adults will behave consistently with their values and towards the environment [92].…”
Section: The Influence Of Value Attitudes On the Ecological Approachmentioning
confidence: 99%
“…Parents who involve their children in the decisions of family affairs in this way not only provide social competences, but also by adopting the values of parents they contribute to environmentally-friendly behavior. Thus, it is likely that young adults will behave consistently with their values and towards the environment [92].…”
Section: The Influence Of Value Attitudes On the Ecological Approachmentioning
confidence: 99%
“…The results of Hickey et al's [42] study demonstrated the impact of parental attitudes on behavioural problems in children. The choice of preferred parenting attitude (as discussed by Gagat-Matuła et al [43]) is dependent on the communication and language skills of the child with an ASD.…”
Section: Discussionmentioning
confidence: 99%